2021
DOI: 10.5468/ogs.21150
|View full text |Cite
|
Sign up to set email alerts
|

Rate of premalignant and malignant endometrial lesion in “low-risk” premenopausal women with abnormal uterine bleeding undergoing endometrial biopsy

Abstract: To determine the incidence of endometrial hyperplasia and endometrial cancer (EH/EC) in low-risk premenopausal women with abnormal uterine bleeding (AUB) undergoing endometrial biopsy and to build a predictive model that includes clinical variables for predicting EH/EC in these women. MethodsThis retrospective study was conducted between January 2015 and March 2020. All premenopausal women aged <55 years with AUB who underwent endometrial sampling during a specified time period were included. Data regarding ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
(32 reference statements)
1
10
6
Order By: Relevance
“…In the present study, EH/EC was reported at 9.7 (22/254) percent. From previous literatures, prevalence of EH/EC were reported ranging from 4 to 15.7 percent (Sattanakho et al, 2020;Jha et al, 2021;Dhakwa et al, 2021;Soja et al, 2020;Kumari et al, 2022). Our prevalence of EH/EC was within the range of previous works above.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the present study, EH/EC was reported at 9.7 (22/254) percent. From previous literatures, prevalence of EH/EC were reported ranging from 4 to 15.7 percent (Sattanakho et al, 2020;Jha et al, 2021;Dhakwa et al, 2021;Soja et al, 2020;Kumari et al, 2022). Our prevalence of EH/EC was within the range of previous works above.…”
Section: Discussionsupporting
confidence: 85%
“…Age and BMI of Jha and current study looked similar. Heavy menstrual bleeding of Jha and the current study were 86.9 (941/1084) and 40.9 (104/254) percent, respectively (Jha et al, 2021). The pattern of bleeding in Jha and current study were different.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…A recent study from India reported that BMI ≥25 kg/m 2 increases the risk for EC/AEH in premenopausal women with AUB. 15 In our study, obesity was defined as BMI ≥25 kg/m 2 , which is suitable for Asian population characteristics.…”
Section: Discussionmentioning
confidence: 99%